WORM INVASIONS IN CHILDREN: EPIDEMIOLOGY, CLINICAL MANIFESTATIONS, DIAGNOSIS AND TREATMENT - Ibatova, Шоира; Abdullaeva, Мавжуда (International Journal of Scientific Pediatrics, 2025)
Worm infestations remain a pressing problem in pediatric medicine, affecting a significant number of children worldwide. Their high prevalence is due to insufficient sanitary culture, low awareness of parents and health workers about prevention methods, as well as the adaptive mechanisms of parasites that allow them to avoid the body's immune response and increase resistance to drugs. The article discusses the main types of helminthic invasions in children, including enterobiasis, ascariasis, toxocariasis, ankylostomiasis, opisthorchiasis, taeniasis and taeniarinhoz. Particular attention is paid to the epidemiological features of these diseases, the influence of climatic and social factors on their prevalence. The pathogenesis of helminthiasis is associated with the migration of parasites throughout the body and the release of toxins, which leads to inflammatory, allergic and intoxication reactions. Clinical manifestations of helminthic invasions vary depending on the type of pathogen, the intensity of infection and the state of the child's immune system. The most common symptoms include gastrointestinal disorders (abdominal pain, nausea, diarrhea), allergic reactions (skin rashes, itching, bronchospasm), neurological disorders (irritability, sleep disturbances, decreased concentration), anemia and nutritional deficiencies. In severe cases, damage to the lungs, liver and central nervous system is possible. Diagnosis of helminthiasis includes microscopic examination of feces, serological tests (ELISA, PCR), blood tests and instrumental methods (ultrasound, MRI). Modern therapy is based on the use of anthelmintic drugs such as mebendazole, albendazole, pyrantel, praziquantel and levamisole. Adjuvant therapy includes antihistamines, enterosorbents, probiotics and iron preparations in the development of anemia. Prevention of helminthic invasions requires compliance with the rules of personal hygiene, heat treatment of food, deworming of pets and regular medical screening of children from risk groups. An integrated approach to diagnosis, treatment and prevention can reduce the prevalence of helminthiasis and prevent their negative impact on children's health.